The Muslim communities’ influence on domestic politics in Northern Europe - Patapeika, Pavel A. (Journal of the Belarusian State University. International Relations, 2024)
The study considers the political implications of a soaring Muslim community in Northern Europe, often viewed as a model for the rest of the European Union. It is shown that massive immigration challenging the foundations of the Scandinavian welfare state and its multiculturalist policy, and some aspects of the Scandinavian experience are also of practical significance to Belarus. The thrust of the argument is that multiculturalism is failing, and Scandinavia should begin to look for other alternatives.